Legal and Organizational Situation in Agriculture of The Virovitica County and The City of Osijek in The Second Half of The 18 Th Century - Haman , Daniel; Iljkić , Darko; Varga, Ivana (Vallis Aurea, 2021)
The Treaty of Karlowitz signed in 1699 concluded the rule of the Ottoman Empire in most parts of Central and Eastern Europe. Liberation of Osijek in 1687, and consequently of whole Slavonia in 1699 brought a new era of freedom and prosperity to its citizens. At least for a short time, since the Habsburg Monarchy re-established their rule over the country by bringing feudal laws and regulations back into force. Austrian empress and Hungarian-Croatian Queen Maria Theresa united Slavonia with Croatia, and re-established the counties of Virovitica, Požega and Syrmia, meaning that the regional administration of Slavonia was completely relinquished to the civil authorities.